The information content of implied volatilities and model-free volatility expectations: Evidence from options written on individual stocks - Stephen J. Taylor; Pradeep K. Yadav; Yuanyuan Zhang (University of Cologne, Centre for Financial Research (CFR), 2009)
The volatility information content of stock options for individual firms is measured using option prices for 149 U.S. firms and the S&P 100 index. ARCH and regression models are used to compare volatility forecasts defined by historical stock returns, at-the-money implied volatilities and model-free volatility expectations for every firm. For one-day-ahead estimation, a historical ARCH model outperforms both of the volatility estimates extracted from option prices for 36% of the firms, but the option forecasts are nearly always more informative for those firms that have the more actively traded options. When the prediction horizon extends until the expiry date of the options, the option forecasts are more informative than the historical volatility for 85% of the firms. However, the model-free volatility expectations are generally outperformed by the at-the-money implied volatilities.
Keywords: C22; C25; G13; G14; 330; Volatility; Stock options; Information content; Implied volatility; Model-free volatility expectations; ARCH models; Volatilität; Aktienoption; Informationswert; ARCH-Modell; USA